Optimizing the Use of Microsoft Office to Support Student Performance and Productivity at SMKI 1 Sukorejo - Heru Setiadi; Eka Afandi; Zaehol Fatah (RAM PUBLISHER, 2025)
In today's digital and globalized era, mastery of information and communication technology, particularly office applications like Microsoft Office, is crucial for both business and education. Today's students are expected to be able to manage information using Word, Excel, and PowerPoint, in addition to understanding course material. However, many students still lack the skills to fully master these applications, even though these skills are essential for completing schoolwork and meeting the demands of the workplace. Therefore, providing Microsoft Office training and mentoring in schools, particularly at SMK Negeri 1 Sukorejo, is an effective way to improve students' digital literacy and prepare them for the ever-innovating technological developments in the corporate sector